THE CULTURE IDENTITY OF INDONESIAN IN A MOVIE OF RAYA AND THE LAST DRAGON - Fiona Puspitasari Mulyadi; Luthfi Nasiroh Khoirun; Marginingsih Marginingsih (Universitas Duta Bangsa Surakarta, 2023)
Culture is a part and identity of a country that owns it, in Raya animation which is a Disney-made animation made by combining cultures from Southeast Asia. The movie Raya and the Last Dragon can be a means to reflect on the values and perspectives of life related to aspects of locality. This movie also talks about various cultures. Therefore, this research aims to find Indonesia's cultural identity and the message conveyed from the movie with the title